Sigmoid colon perforation complicating neonatal rectovestibular fistula: A case report - Partogi Napitupulu; Nadifa Agil; Revalita Wahab; Nathalia Ningrum (Institute of Computer Science (IOCS), 2026)
Anorectal malformation (ARM) with rectovestibular fistula may allow small amounts of meconium to pass despite ongoing distal bowel obstruction. We report a three-day-old term female neonate with an imperforate anus, progressive abdominal distension, bilious vomiting, and minimal meconium passage through a rectovestibular fistula. Abdominal radiography showed marked bowel dilatation and pneumoperitoneum. Emergency laparotomy revealed sigmoid colon perforation with diffuse fecal peritonitis. The perforation was repaired, followed by a double-barrel sigmoid colostomy. The infant recovered well and was discharged on postoperative day eight. At three-month follow-up, the wound was completely healed and the colostomy remained healthy and functional. This case illustrates a rare but serious complication of rectovestibular fistula, in which limited meconium passage may coexist with significant bowel obstruction and subsequent perforation. These findings emphasize that thorough perineal inspection, high vigilance for obstruction despite minor meconium passage, and timely surgical intervention are essential to prevent bowel perforation in neonates with anorectal malformations.